The Endocannabinoid System in Amyotrophic Lateral Sclerosis - Bilsland, Lynsey G.; Greensmith, Linda (Current Pharmaceutical Design, 2008)
Amyotrophic Lateral Sclerosis (ALS) is a fatal neurodegenerative condition characterised by the selective loss of motor neurons from the spinal cord, brainstem and motor cortex. Although the pathogenic mechanisms that underlie ALS are not yet fully understood, there is significant evidence that several neurotoxic mechanisms including excitotoxicity, inflammation and oxidative stress, all contribute to disease pathogenesis. Furthermore, recent results have established that although primarily a motor neuron specific disorder, ALS is not cell-autonomous and non-neuronal cells including astroglia and microglia play a critical role in mechanism of disease. Currently the only licensed therapy available for the treatment of ALS is the anti-glutamatergic agent Riluzole, which has limited therapeutic effects. However, there is increasing evidence that cannabinoids and manipulation of the endocannabinoid system may have therapeutic value in ALS, in addition to other neurodegenerative conditions. Cannabinoids exert anti-glutamatergic and anti-inflammatory actions through activation of the CB1 and CB2 receptors, respectively. Activation of CB1 receptors may therefore inhibit glutamate release from presynaptic nerve terminals and reduce the postsynaptic calcium influx in response to glutamate receptor stimulation. Meanwhile, CB2 receptors may influence inflammation, whereby receptor activation reduces microglial activation, resulting in a decrease in microglial secretion of neurotoxic mediators. Finally, cannabinoid agents may also exert anti-oxidant actions by a receptor-independent mechanism. Therefore the ability of cannabinoids to target multiple neurotoxic pathways in different cell populations may increase their therapeutic potential in the treatment of ALS. Recent studies investigating this potential in models of ALS, in particular those that focus on strategies that activate CB2 receptors, are discussed in this review.
Keywords: excitotoxicity